3-Core Fiber Modal Analysis - Benedicto, David; Vallés, Juan Antonio (Jornada de Jóvenes Investigadores del I3A, 2017)
Multicore fibers (MCFs) are expected as a good candidate for overcoming the capacity limit of current optical communication systems. This paper describes the modal analysis of a 3-core MCF taking into account some geometrical and material degrees of freedom. A reasonable tailoring of the modal distribution is shown to be achievable.